Reliugisitas Pada Waria Usia Muda - Rahmawati Rahmawati; Hadariansyah Hadariansyah; Imadduddin Imadduddin (Jurnal Studia Insania, 2021)
Regardless of identity, transvestites are also human beings who must have the character to be pious. A human being with faith can be seen from how obedient he is to God or also called religiosity. Transsexual life in Banjarmasin is not very visible in the community, but in its community religious activities themselves continue to be carried out. This type of research is field research using a qualitative approach and case studies because the phenomenon of adolescent transsexual religiosity is unique to study. Data collection techniques used were the scale of religiosity, semi-structured interviews, and non-participant observation with subjects totaling two people with characteristics of transsexuals who were 18-21 years old, Muslim, were members of the IWB community and Paris Barantai, and lived in the Banjarmasin area. Both subjects have a high level of religiosity. It can also be seen that there are five dimensions of religiosity in transvestites, where both have a size of faith in a strong pillar of hope, an aspect of worship in doing fewer religious duties, a relatively good spiritual dimension, quite a proportion of religious knowledge because they at least know the basics religion, lack of practice in relations with the community and relationships with God, and the factors that influence their religiosity are the main factors, namely social influence and need elements as supporting factors.